In a question I've got, I found that I need to prove the following equality:

$\lim_{h\rightarrow 0}\int_{0}^{\infty}\frac{e^{-(t+h)x}-e^{-tx}}{hx}dx=\int_{0}^{\infty}\lim_{h\rightarrow 0}\frac{e^{-(t+h)x}-e^{-tx}}{hx}dx$ ($t>0$ is a constant.)

I know the limit in the right side is $-e^{-tx}$ if that matters.

Now, by Heine, it's sufficient to prove this result with a sequence $h_n\rightarrow 0$ instead of a continuous variable. So let's define $f_n(x)=\frac{e^{-(t+h_n)x}-e^{-tx}}{h_nx}$ and now we need to show that the conditions of DCT hold, and all that's left is finding a dominating function.

That's where I failed. Any idea?

  • 1
    $\begingroup$ Since $\lim_{h_n\to 0}\big|\frac{e^{-h_nx}-1}{h_nx}\big|=1$, then for sufficiently large $n$ we have $\big|\frac{e^{-h_nx}-1}{h_nx}\big|<2$. You could take the dominating function to be $2e^{-tx}$. $\endgroup$ – M. T Aug 30 '16 at 15:55
  • $\begingroup$ Thank you! didn't see that $\endgroup$ – 35T41 Aug 30 '16 at 16:00
  • $\begingroup$ @35T41 My answer is not complete . . . see the one by Dr. M V for a complete one $\endgroup$ – user288742 Aug 31 '16 at 1:21
  • $\begingroup$ I would prefer if you unaccepted mine and accepted his $\endgroup$ – user288742 Aug 31 '16 at 1:29
  • $\begingroup$ Done. I actually used M.T's answer eventually... but thank you anyway $\endgroup$ – 35T41 Aug 31 '16 at 8:01

A very efficient way forward circumvents use of the Dominated Convergence Theorem and instead exploits Frullani's Theorem. Proceeding, we obtain

$$\frac1h \int_0^\infty \frac{e^{-(t+h)x}-e^{-tx}}{hx} \,dx=\frac1h \log\left( \frac{t}{t+h}\right)$$

The limit as $h\to 0$ is straightforward to evaluate with the answer $-\frac1t$. And we are done!

If one wishes to proceed through use of the Dominated Convergence Theorem, then the following primer will facilitate analysis.


In THIS ANSWER, I showed using only the limit definition of the exponential function and Bernoulli's Inequality that the exponential function satisfies the inequalities

$$\bbox[5px,border:2px solid #C0A000]{1+x\le e^x\le \frac{1}{1-x}} \tag 1$$

for $x<1$.

Herein, we use the inequality on the left-hand side of $(1)$ to establish a coveted dominating function. To that end, we proceed.

Note that we can write the integrand $\frac{e^{-(t+h)x}-e^{-tx}}{hx}$ as

$$\begin{align} \frac{e^{-(t+h)x}-e^{-tx}}{hx}&=e^{-tx}\left(\frac{e^{-hx}-1}{hx}\right) \tag{2a}\\\\ &=e^{-(t+h)x}\left( \frac{1-e^{hx}}{hx} \right) \tag{2b} \end{align}$$

Note that the term in parentheses on the right-hand side of $(2a)$ is non-positive for all $x\in [0,\infty$ and all $h$. Applying the left-hand side inequality in $(1)$ to $(2a)$, we find immediately that for $h>0$

$$\left|\frac{e^{-hx}-1}{hx}\right|\le 1$$

for $x\ge 0$, $h>0$.

For $h<0$, we take $|h|<t/2$. Then, applying the left-hand side inequality in $(1)$ to $(2b)$, we see analogously that

$$\left| \frac{1-e^{hx}}{hx} \right|\le 1$$

for $x\ge 0$, $h<0$.

Hence, we have

$$\left|\frac{e^{-(t+h)x}-e^{-tx}}{hx}\right|\le e^{-tx/2}$$

for all $x\ge 0$ and all $|h|\le t/2$.

Inasmuch as $\int_0^\infty e^{-tx/2}\,dx=\frac2t <\infty$, the Dominated Convergence Theorem guarantees that

$$\begin{align} \lim_{h\to 0}\int_0^\infty \frac{e^{-(t+h)x}-e^{-tx}}{hx}\,dx&=\int_0^\infty \lim_{h\to 0}\left(\frac{e^{-(t+h)x}-e^{-tx}}{hx}\right)\,dx\\\\ &=-\int_0^\infty e^{-tx}\,dx\\\\ &=-\frac1t \end{align}$$

And we are done!

  • $\begingroup$ I have been thinking about this question . . . Is there an issue with the dominating function only holding for $|h| \le t/2$? I guess I am not familiar with the intricacies of LDCT when you don't have a limit as $n \to \infty$ of an integral of some sequence $(f_n)_{n=1}^\infty$. $\endgroup$ – user288742 Aug 31 '16 at 3:08
  • $\begingroup$ Good question. There is no conceptual problem ensuring that $|h|<t/2$ since we eventually let $h \to 0$. $\endgroup$ – Mark Viola Aug 31 '16 at 3:11
  • $\begingroup$ Ok. I thought issues might arise, since I know that in the "sequential version" you must have $|f_n(x)| \le g(x)$ for all $n$ in order to say $g$ is a dominating function. Or maybe this only needs to hold for sufficiently large $n$ as well? $\endgroup$ – user288742 Aug 31 '16 at 3:15
  • $\begingroup$ The latter statement is correct. We only require that there is an $N$ such that $|fn(x)|\le g(x)$ for all $n>N$. $\endgroup$ – Mark Viola Aug 31 '16 at 3:22
  • $\begingroup$ Thanks - that is good to know ! $\endgroup$ – user288742 Aug 31 '16 at 3:24

Fix $h >0$. Note that $$ \frac{e^{-(t+h)x}-e^{-tx}}{hx} = e^{-tx} \left( \frac{e^{-hx}-1}{hx} \right) \implies \left\vert \frac{e^{-(t+h)x}-e^{-tx}}{hx} \right\vert = e^{-tx} \left\vert \frac{e^{-hx}-1}{hx} \right\vert $$

Now, define $f(x) = e^{-x}$. Then $$\frac{e^{-hx}-1}{hx} = \frac{f(hx) - f(0)}{hx}$$ and by Mean Value Theorem $$ \frac{f(hx) - f(0)}{hx} = f'(\xi_x) = -e^{-x} \Big|_{x = \xi_x} = -e^{-\xi_x} $$ for some $\xi_x \in (0,hx)$. Now define $g(y) = -e^{-y}$ for $y>0$. It is clear that $|g(y)| < 1$ for all $y >0$.

So for all $x$ we have $$ \left\vert \frac{ f(hx) - f(0)}{hx} \right\vert = |-e^{-\xi_x}| \le 1 $$

which means $$ \left\vert \frac{e^{-(t+h)x}-e^{-tx}}{hx} \right\vert = e^{-tx} \left\vert \frac{e^{-hx}-1}{hx} \right\vert \le e^{-tx} $$ and the RHS is integrable on $[0,\infty)$.

EDIT: If $h<0$, then write $$ \frac{e^{-(t+h)x}-e^{-tx}}{hx} = e^{-(t+h)x} \left( \dfrac{ 1 - e^{hx}}{hx} \right)$$ and $$ \dfrac{ 1 - e^{hx}}{-hx} = \dfrac{ g(0)- g(hx)}{-hx} $$ where $g(x) = e^{x}$. Then, by MVT we get $$\dfrac{ g(0)- g(hx)}{-hx} = g'(\xi_x) = e^{\xi_x} $$ for some $\xi_x$ in $(hx,0)$. Then, $e^{\xi_x} \le 1$ because of this interval.

We can further restrict ourselves to $-\frac{t}{2} < h < 0$, since we're taking a limit and only care about small $h$. Finally $$ \left\vert e^{-(t+h)x} \left( \dfrac{ 1 - e^{hx}}{hx} \right) \right\vert \le e^{-(t+h)x} \le e^{-tx/2} $$ and this serves as a dominating function.

  • 1
    $\begingroup$ This doesn't apply when $h<0$. So, you have proven convergence from the right only. ;-) $\endgroup$ – Mark Viola Aug 30 '16 at 21:21
  • $\begingroup$ I would delete but I can't since it's accepted. My apologies $\endgroup$ – user288742 Aug 31 '16 at 1:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.